COMPETENCY ANALYSIS OF EMPLOYEE AGENCY AND HUMAN RESOURCES DEVELOPMENT IN SUMEDANG DISTRICT 2023 - Ade Irawan (Jurnal Scientia, 2023)
The most needed resource in the organization is human resources. Employees are the most important human resource or organizational asset in achieving the vision, mission and goals of the organization. To improve the performance of employees in the organization, it must be supported by several components, one of which is competence. Carrying out basic tasks and functions in an organization with the human element is very important, because humans are one of the factors that play a role in organizations, both government and non-government organizations. The role of humans is very decisive in achieving organizational goals, so that activities and existence can run well, it is necessary to seriously manage Human Resources through a work rule and order as one of the methods in carrying out its activities, in order to be able to answer a global challenge from competition. which is getting higher. Employee competence is referred to as the basic character possessed by a person to demonstrate the ability of employees to excel in a job to achieve optimal work results. In this regard, it is necessary to support the capabilities of various resources, especially the human resources of good government officials, so that the implementation of tasks can be achieved in an efficient and effective manner.